Analisis Kebutuhan Pengembangan Multimedia Pembelajaran IPAS Berbasis Articulate Storyline 3 untuk Penguatan Literasi Sains Siswa Sekolah Dasar - Diva Auliya Fajrin; Alfi Laila; Mumun Nurmilawati (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Scientific literacy needs to be strengthened from an early stage because it serves as a fundamental competence for elementary school students to understand natural phenomena logically, critically, and based on evidence. However, science and social studies (IPAS) learning in elementary schools still faces several challenges, particularly in the topic of changes in the states of matter, which is relatively abstract and difficult for students to understand when delivered only through textbooks or verbal explanations. This study aimed to analyze the need for developing IPAS learning multimedia based on Articulate Storyline 3 as a solution to support the enhancement of scientific literacy among elementary school students. The study employed a descriptive approach with a mixed-methods design as the initial analysis stage of the ADDIE development model. The participants consisted of 2 fourth-grade teachers and 40 fourth-grade students from SDN Gayam 2 and SDN Gayam 3 in Kediri City. Data were collected through observation, in-depth interviews, and needs analysis questionnaires using a Likert scale. The results showed that students had a high need for interactive learning media, as indicated by the percentage of knowledge about digital media (74%), difficulties in understanding the topic of changes in the states of matter (75%), supporting factors for media use (82%), barriers to media use (69%), and expectations for interactive learning media (81%). From the teachers’ perspective, the percentages were 83% for knowledge of learning media, 85% for mastery of IPAS content, 78% for school support toward digital media, 77% for barriers to media development, and 94% for expectations of ready-to-use media. These findings indicate a strong need for the development of IPAS learning multimedia based on Articulate Storyline 3 that is interactive, visual, and contextual to help students understand the concept of changes in the states of matter while also supporting the improvement of scientific literacy in elementary schools.